2017
DOI: 10.1371/journal.pone.0175537
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with malaria parasitaemia in children under the age of five years in Malawi: A comparison study of the 2012 and 2014 Malaria Indicator Surveys (MISs)

Abstract: BackgroundMalaria is the main cause of morbidity and mortality among children under the age of five years in Malawi. The aim of this study was to compare the prevalence and factors associated with malaria parasitaemia among children under the age of five years in Malawi between the 2014 and 2012 Malaria Indicator Surveys (MISs).MethodologyData on demographic factors, vector control interventions, and blood for malaria test were collected from a representative sample of children under the age of five years in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
52
2
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 29 publications
25
52
2
1
Order By: Relevance
“…Furthermore, this study found that children who were over two years old had higher odds of being diagnosed with malaria infection than younger children. This is consistent with other studies which reported that malaria prevalence increases with child age (37,38). This may be because younger children in Malawi share a bed with their mothers and are more likely to be covered properly with a blanket or mosquito net than older children.…”
Section: Discussion and Implicationsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, this study found that children who were over two years old had higher odds of being diagnosed with malaria infection than younger children. This is consistent with other studies which reported that malaria prevalence increases with child age (37,38). This may be because younger children in Malawi share a bed with their mothers and are more likely to be covered properly with a blanket or mosquito net than older children.…”
Section: Discussion and Implicationsupporting
confidence: 92%
“…We selected potential covariates of child malaria infection in our model based on current literature in Malawi and other countries in SSA (16)(17)(18)(19)(20)(21). These were characteristics of the children, who were our study population, characteristics of the parents that in uence childcare practices and characteristics of the household.…”
Section: Explanatory Variablesmentioning
confidence: 99%
“…14 The present study is similar to another study conducted in Mali; the prevalence increased from the previous years, however many interventions in children under 5 years old. 15 In contrast, a study which was conducted in villages surrounding Lake Langano, Oromia region, Ethiopia showed a much higher prevalence of malaria 66.4%. 16 This difference might be seasonal variation for high prevalence of malaria parasite in the study site.…”
Section: Discussionmentioning
confidence: 91%
“…A child's age affects their exposure and risk of malaria; for example older children had greater malaria prevalence in Malawi (Zgambo et al, 2017), which that study's authors attributed to older children's greater independence and time spent outdoors during evening hours. We included as a control variable the child's age as a binary variable for each year between zero and four to allow for potential non-linear effects.…”
Section: Datamentioning
confidence: 95%